Effectiveness of Budgetary Controls on Budget Execution in Zanzibar - Said Salum, Hawa; Daffay, Mamudu (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims at examining the effectiveness of budgetary controls on budget execution in Zanzibar. The proper linkages between public resources and its management through service delivery are the key to success of any government. The study adopted descriptive research design in which primary data was collected by the use of questionnaire. More over the study used a stepwise approach to generate model, where regression model was used to analyze the degree of the relationship between budgetary control and the extent to which it contribute to the performance of budget in Zanzibar. The results reveals that a budgetary control as perceived by various respondents is effective on the basis of planning and budgeting, monitoring and control, analyzing and feedback and thus concluded to have a positive relationship with budget performance. Based on the study, it is recommended that management should be ready to participate in budget execution process in order to remove the existing challenges.